Maihime = Die Tänzerin - Shinoda, Masahiro 1931-2025; Gō, Hiromi 1955-; Wolf, Lisa (Terebi Asahi, 1989)
Based on the novel by Mori Ōgai, it is a story of a young man, Ota Toyotaro, who is sent to Berlin by the Japanese government for a program of study. There by chance he meets and befriends a young girl names Alice, and, despite a severe upbraiding by his superiors, he begins living with her. The film, coproduced by Japanese and German staff is a love story that transcends national borders
Keywords: Mori, Ōgai / 1862-1922 / Film adaptations; Motion pictures, German; Motion pictures, Japanese